PENGEMBANGAN MODEL ESTIMASI UMUR TANAMAN SAWIT DENGAN MENGGUNAKAN DATA LANDSAT-TM - Jansen Sitorus (Indonesian National Institute of Aeronautics and Space (LAPAN), 2004)
Oil Palm Plantation (Elaelis Guineensis Jacq), in its growth will undergo physical change so that it can be monitored by remote sensing data, that is by observing the influence of age towards spectral band reflectance or indices that can be obtained from Landsat-TM data. The analysis shows Landsat spectral band that correlates with oil palm plantation's age is Band-5 (r=-0.75), Band-7 (r=-0.52), Band-4 (r=-0.50). The indices that correlate with oil palm plantation's age is ratio Band 5/3 (r=-0.71), IRI (r=-0.56) and MIRI-1 (r=-0.48). NDVI and IRI do not correlate with the plantation's age. From the research carried out towards several function froms between age and oil palm plantation a good relationship is obtained on multi-regression linear function (R2 = 0.69), where the equation is: Y=61.3- 0.54 XI + 39.39 X2-42.31 X3, (Xi more than 0), where Y : age, X1=B5, X2=IRI dan X3=MIRI1 (untuk α = 0.05)